The day-of-the-week: effect on South African REITs - Hillen, D T (My University, 2021)
Background to the study: Calendar anomalies are described as theoretical patterns of abnormal returns of listed stock at certain dates or periods during a calendar year (Jadevicius & Lee, 2016).This suggests that there is an element of predictability in achieving above average returns as an investor using publicly available information. These anomalies have attracted much attention in the past, and have become well documented across many markets beginning with Bachelier (1900) which is regarded as the first research to have identified that calendar related inconsistencies existed (Davis & Etheridge, 2006). Bachelier“ examined whether the process [of] generating stock returns operates continuously or only during active trading, i.e. Monday to Friday” (Jadevicius & Lee, 2016, page 59). This has led to many more studies regarding calendar anomalies, see inter alia,Clark (1973), French (1980), French & Roll (1986), Thaler (2012), Davis & Etheridge (2006) & Jadevicius & Lee, (2016), Kinatede, Weber, & Wagner (2019), Aman, Natchimuthu, & Lavanya (2019), and Khan & Rabbani, (2019). As we will discuss later, many of these studies have had contradictory and mixed results... The day-of-the-week is the term applied when a specific day of the week produces abnormal stock returns compared to other days of the week Fakhry (2016). The January effect refers to a calendar anomaly whereby the prices of share returns are higher in January than in other months of the year Harjula (2019). The turn-of-the-month effect refers to the temporary increase in share prices in the last few days and first few days of each month of the year Kotlebova (2019), and the Holiday effect, which is one of the most widely researched calendar anomalies, is the term applied to observed patterns around holidays and more specifically, the increased returns on the few days leading up to major holidays Chancharat, et al., (2018)...
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in the field of Property Development and Management, 2021